2003
DOI: 10.1001/jama.290.18.2428
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Improving Depression Care on Pain and Functional Outcomes Among Older Adults With Arthritis

Abstract: STEOARTHRITIS IS THE MOSTcommon type of arthritis among older adults. 1 Its prevalence increases sharply with age. About one third of individuals older than 65 years experience symptomatic osteoarthritis of the knee, and almost 80% of persons have degenerative joint disease after age 70 years. [2][3][4] Arthritis is a leading cause of disability for older persons, reduces quality of life, and accounts for one eighth of all restricted activity days. 5,6 The combined medical and economic costs associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
373
2
15

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 570 publications
(396 citation statements)
references
References 53 publications
6
373
2
15
Order By: Relevance
“…In our study sample, adults with depression had higher rates of co-existing CVD 29,30 It is also evident from the results of a systematic review of 45 studies that receiving collaborative care as compared to usual care has been found to be beneficial among those with major depressive disorder for improving the treatment outcomes such as adherence and functional status, and for reducing the financial burden. 31 It has to be noted that the demonstration projects for providing coordinated care for high-cost and highneed patients have also proven to be cost-effective.…”
Section: Discussionmentioning
confidence: 63%
“…In our study sample, adults with depression had higher rates of co-existing CVD 29,30 It is also evident from the results of a systematic review of 45 studies that receiving collaborative care as compared to usual care has been found to be beneficial among those with major depressive disorder for improving the treatment outcomes such as adherence and functional status, and for reducing the financial burden. 31 It has to be noted that the demonstration projects for providing coordinated care for high-cost and highneed patients have also proven to be cost-effective.…”
Section: Discussionmentioning
confidence: 63%
“…Poor mental health has been associated with worse overall hip and knee OA pain and deterioration in mental health has been found to precede short term exacerbations of OA pain (30). Treatment of depression in people with arthritis appears to improve depressive symptoms, reduce OA pain, improve function and quality of life (31) and therefore is an important consideration in the management of OA.…”
Section: Psychological Factorsmentioning
confidence: 99%
“…5 A growing number of studies of collaborative care management for depression in a wide range of health care systems, including the Veterans Health Administration (VA), show that it is more effective than usual care. [6][7][8][9][10][11] In particular, Gilbody et al conducted a comprehensive systematic review of 37 randomized trials involving 12,355 patients with depression who received primary care with integrated collaborative care. The review confirms that collaborative care, when utilized in addition to primary care, is more effective than traditional standard care in the short term, and strongly suggests that it may be more effective in the long term.…”
Section: Introductionmentioning
confidence: 99%